Eksplorasi Alasan Kunci Sukses Social Media Influencer Bisnis dan Pemasaran di Indonesia - Maulana, Dimas (Research Center and Case Clearing House (RC-CCH) - Sekolah Tinggi Manajemen PPM, 2023)
This research aims to identify the critical factors contributing to Social Media Influencers' (SMI) success in managing their career as content creators. This study involved observing 46 SMI accounts on Tik Tok and Instagram and analyzing the engagement rate as a performance metric for SMIs. A descriptive qualitative method was employed, and data was gathered using analisa.io as a social media analysis platform. The findings suggest that an SMI's success can be attributed to the identity group, primary platform, content pillars, number of weekly posts, content monetization, and hashtag usage. Conversely, this study did not establish a correlation between many followers and decreased performance. The results are intended to inform future research and foster a more profound understanding of SMIs.